Who Are The Workers Impacted By The Covid-19 Pandemics? An Analysis of the National Labor Force Survey in Central Sulawesi - Karim, Farashintha Julhija; Kasnawi, Tahir; Madris, Madris (Budapest International Research and Critics University, 2021)
The Covid-19 pandemic is a global problem that has a negative impact on the employment sector. Many workers become unemployed or experience reduced working hours due to the impact of company policies. According to BPS (2020), in August 2020 the unemployment rate increased by 0.66 points or by 12.39 thousand people compared to the previous year. This problem also occurs in Central Sulawesi. This study examines individual characteristics and job characteristics inherent in workers in Central Sulawesi based on status affected by the Covid-19 pandemic. Using data from the National Labor Force Survey (Sakernas) and using a quantitative approach, this study examines the impact of the Covid-19 pandemic on workers based on their characteristics. We applied a descriptive analysis using a contingency table to calculate the proportion, relative risk (RR), and odds ratio (OR). The results obtained are that the workers affected by the COVID-19 pandemic are mostly adult workers, educated workers, formal workers, working in the tertiary sector, and coming from urban areas.